2021
DOI: 10.1093/tropej/fmab039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Children Diagnosed Dengue-Associated Acute Liver Failure with or without N-Acetylcysteine Treatment: A Retrospective Cohort Study

Abstract: Objectives N-acetylcysteine (NAC) has been shown to prevent hepatic damage and improve microcirculatory blood flow and oxygen delivery to the tissue. Previous studies have proposed the benefit of NAC in dengue-associated acute liver failure (ALF). However, most studies are descriptive and lack comparison between groups. We aimed to compare the ALF resolution rate and mortality rate of those who received and did not receive NAC treatment. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…Some of the centers have used NAC in adults with variable results but it is not part of our management protocol and its use was sporadic (21,22). We did not find any significant difference in survival with the use of NAC though Sriphongphankul et al (16) from Thailand found it to be beneficial in dengue PALF. There are occasional case reports of liver transplantation in dengue ALF in adults but in our series, we did not do any (23).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Some of the centers have used NAC in adults with variable results but it is not part of our management protocol and its use was sporadic (21,22). We did not find any significant difference in survival with the use of NAC though Sriphongphankul et al (16) from Thailand found it to be beneficial in dengue PALF. There are occasional case reports of liver transplantation in dengue ALF in adults but in our series, we did not do any (23).…”
Section: Discussioncontrasting
confidence: 73%
“…Hence, dengue ALF needs to be considered in the differential diagnosis of any ALF in endemic areas. In adult patients, the onset of ALF has been observed at a median of 7.5 days (5–13 days) after the inception of fever but in a recent pediatric series, it was 6.3 days (15,16). This is the usual time when derangement in liver enzymes peaks (3).…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited definitive evidence outside of acetaminophen overdose, 21 NAC is postulated to provide cytoprotective benefits in acute liver failure via replenishing glutathione, scavenging free radicals, and bolstering hepatic regeneration 22 . Studies indicate improved survival with NAC in severe dengue with liver failure 22,23 . While evidence remains scarce, ursodeoxycholic acid's (UDCA) role in idiosyncratic DILI deserves exploration based on existing systematic reviews showing favorable biochemical parameters 24 .…”
Section: Discussionmentioning
confidence: 99%
“… 22 Studies indicate improved survival with NAC in severe dengue with liver failure. 22 , 23 While evidence remains scarce, ursodeoxycholic acid's (UDCA) role in idiosyncratic DILI deserves exploration based on existing systematic reviews showing favorable biochemical parameters. 24 Further high‐quality randomized controlled trials are necessary to determine whether regimens combining NAC and UDCA offer additive hepatoprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic involvement is characterized by numerous clinical manifestations, ranging from asymptomatic elevations in serum transaminases to ALF 23 . Although the pathogenesis of liver injury secondary to dengue virus infection remains unclear, potential mechanisms include apoptosis in hepatocytes and Kupffer cells, immune‐mediated hepatocyte injury, and shock‐induced ischemic hepatitis 24 . Currently, there is no specific treatment for dengue‐associated ALF; affected patients receive supportive care and measures to prevent further complications.…”
Section: Flavivirusmentioning
confidence: 99%